The instrumental consort repertory of the late fifteenth century - Banks, Jon (Ashgate, 2006)
Introduction : what instrument consort repertory? -- Lutes, players, and the humanist tradition -- Defining the repertory -- The textless chansonniers : repertory, compilation, and use -- Instrumental items in mixed sources -- Epilogue